An improved 2DPCA for face recognition under illumination effects - Woraratpanya, Kuntpong; Sornnoi, Monmorakot; Leelaburanapong, Savita; Titijaroonroj, Taravichet; Varakulsiripunth, Ruttikorn; Kuroki, Yoshimitsu; Kato, Yasushi (My University, 2015)
Principal component analysis (PCA) is one of the successful techniques for applying to face recognition, but its challenge still remains for solving an illumination effect condition. This paper proposes an improved 2DPCA (I-2DPCA) for overwhelming the illumination effect in face recognition. The proposed method is based on two assumptions. The first assumption is to create the covariance matrix that can effectively decompose the components of illumination effects from the eigenfaces. This avoids the illumination effect problem. The second assumption is to select the suitable eigenvectors that can significantly improve the recognition rate. Based on the Extended Yale Face Database B+ containing 60 illumination conditions, the experimental results show that not only does the proposed method decrease the computing time, but it also improves the recognition rate up to 95.93%.
Keywords: (2D)2PCA; 2DPCA; Face Recognition; I-2DPCA; Illumination Effects; PCA